2024
DOI: 10.3390/pathophysiology31010003
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Catheter-Based Irreversible Electroporation for Ventricular Tachycardia

Matthew Leonard Repp,
Ikeotunye Royal Chinyere

Abstract: The use of catheter-based irreversible electroporation in clinical cardiac laboratories, termed pulsed-field ablation (PFA), is gaining international momentum among cardiac electrophysiology proceduralists for the non-thermal management of both atrial and ventricular tachyrhythmogenic substrates. One area of potential application for PFA is in the mitigation of ventricular tachycardia (VT) risk in the setting of ischemia-mediated myocardial fibrosis, as evidenced by recently published clinical case reports. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Applications for PFA include both atrial and ventricular arrhythmogenic substrate management. Though first described [1] and clinically approved in Europe [63] for atrial substrate modification, preclinical ventricular PFA data have suggested more favorable and homogeneous lesion characteristics in both normal and scarred ventricular myocardium [64][65][66][67] . However, additional preclinical and clinical evaluation is still necessary to clarify this potential advantage, relative to thermal catheter-based ablation techniques, namely radiofrequency energy.…”
Section: Efficacy and Coronary Artery Spasm/stenosismentioning
confidence: 99%
“…Applications for PFA include both atrial and ventricular arrhythmogenic substrate management. Though first described [1] and clinically approved in Europe [63] for atrial substrate modification, preclinical ventricular PFA data have suggested more favorable and homogeneous lesion characteristics in both normal and scarred ventricular myocardium [64][65][66][67] . However, additional preclinical and clinical evaluation is still necessary to clarify this potential advantage, relative to thermal catheter-based ablation techniques, namely radiofrequency energy.…”
Section: Efficacy and Coronary Artery Spasm/stenosismentioning
confidence: 99%